Contact fatigue of veneer feldspathic porcelain on dental zirconia. Issue 3 (March 2015) - Rueda, A.O.; Anglada, M.; Jimenez-Pique, E.
Highlights We have tested the fatigue to contact loading of porcelain veneer on zirconia. Results show apparition of cracking under cyclic loads in humid environments. An estimation of lifetime of porcelain coatings under service is provided. Protecting the dental ceramic by a guard could increase the lifetime of the materials.